PENGARUH KINERJA SUMBER DAYA MANUSIA TERHADAP KINERJA PROYEK KONSTRUKSI DI KOTA BUKITTINGGI - Surya Eka Priana (Ensiklopedia of Journal, 2023)
Project human resources (HR) in the field, in this case builders and construction workers, are synonymous with hard sector work, thus providing challenges in their management. However, in this study the authors did it to personnel whose positions were at the upper middle management level in project implementation. The purpose of this study was to analyze HR performance indicators that have a dominant influence on the performance of construction projects in the City of Bukittinggi. Data collection was carried out by survey using a questionnaire which was distributed to 75 respondents who were selected based on the purposive sampling method which included project managers, site managers, site engineers, quantity surveyors, quality control, drafters, programmers, supervisors, and logistics. Data analysis used includes multiple linear regression analysis, multiple correlation analysis, determination test, and t test using the SPSS 24 program. The results of multiple linear regression analysis show that the performance of construction projects is influenced by the performance of human resources. The determination test value (0.89) shows that there is a strong and positive correlation between discipline, initiative, training, motivation, quality, work environment, commitment, responsibility, abilities, and facilities, to project performance. The t test values of each HR performance indicator are discipline (3.86), initiative (-1.52), training (-1.25), motivation (0.60), quality (-1.16), work environment ( 1.66), commitment (2.17), responsibility (-2.96), ability (3.82), and means (3.44). Of these values, discipline is the most dominant indicator affecting project performance.